2005
DOI: 10.1093/bja/aei168
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol does not modify the Bispectral Index during anaesthesia with sevoflurane and remifentanil

Abstract: Tramadol, given with ketorolac to prevent postoperative pain, during anaesthesia maintained with sevoflurane and remifentanil at BIS between 40 and 50, does not modify the BIS value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…As in our study on long-term tramadol use, there was no evidence of increased risk of awareness during general anaesthesia in patients who were given tramadol acutely [16,17]. In these studies, tramadol was administered during sevoflurane-or propofol-remifentanil anaesthesia and no changes were seen in bispectral index.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…As in our study on long-term tramadol use, there was no evidence of increased risk of awareness during general anaesthesia in patients who were given tramadol acutely [16,17]. In these studies, tramadol was administered during sevoflurane-or propofol-remifentanil anaesthesia and no changes were seen in bispectral index.…”
Section: Discussionsupporting
confidence: 49%
“…During the study period, nociceptive stimuli were limited to tetanic stimulation and tracheal intubation, which may have caused lower stress level than skin incision. It has been suggested that EEG-activating effect of tramadol depends on the concentration of the volatile anaesthetics [17]. The fact that we did not find any significant EEG changes associated with regular tramadol use may be partly due to the study protocol resulting in rapid progression to a relatively deep level of propofol-induced hypnosis.…”
Section: Discussionmentioning
confidence: 51%
“…Levando-se em conta os valores médios de BIS obtidos, embora não tenham sido encontradas diferenças significativas, pôde-se observar que o GT apresentou valores mais baixos, permanecendo na faixa de 50, enquanto que no GC, permaneceram próximos a 60, após a administração dos fármacos. Fodale et al (2005), em estudo realizado com humanos anestesiados pelo sevofluorano, também não observaram alteração significativa no BIS depois da administração de tramadol quando comparados à administração de placebo. Esses valores foram mantidos na faixa de 50 para o grupo controle e 40, para o grupo que recebeu o opióide.…”
Section: Resultsunclassified
“…Mildh et al (1999) observaram que tanto a FC como a pressão arterial média (PAM) mantiveram-se estáveis com a administração de 2,1mg/kg, seguida de infusão contínua de 1,2 mg/kg/h. Fodale et al (2005), em estudo realizado com humanos que receberam sevofluorano, não observaram nenhuma alteração nos valores do índice biespectral (BIS), quando comparadas aos que receberam tramadol e placebo. Os efeitos adversos mais freqüentemente encontrados em humanos incluem náuseas, vômito, constipação e xerostomia (Padmasuta, 1987).…”
Section: Introductionunclassified
“…The electroencephalographic (EEG) changes by tramadol have been investigated in dogs and humans [17,18], but only in the anaesthetized state. As far as we know, there has been no report about the effects of different doses of tramadol on EEG, although tramadol has proconvulsive effects.…”
Section: Introductionmentioning
confidence: 99%